Iliopsoas muscle haematoma as mild type A hemophilia in an adolescent (Archives of Pediatrics of Uruguay, 2020)
Introduction: type A hemophilia is an inherited congenital coagulopathy linked to chromosome X, expressed by a decrease in coagulation factor VIII. Its clinical expression is hemorrhage in different locations, mainly joints, muscles and soft tissue.Objective: to describe the clinical case of an adolescent with no previous history of pathology, who consulted for a psoas iliacus haematoma with no apparent cause, as an atypical presentation of mild type A hemophilia.Clinical case: 13 years of age, male, denies previous history of pathology. Practices high impact sports. Consults for coxalgia and pain in left lower limb. Denies trauma. Pain progressively intense, until it prevented patient from walking. Physical examination: intense pain and limitation of active and passive movement of the left hip. Pain at palpation of left iliac fossa. The remaining examination is normal. Pelvic X ray shows no alterations. Pelvic magnetic resonance: solid expansive process in the left psoas iliacus of 110 mm x 50 mm x 60 mm. After this finding, we repeated the anamnesis and discovered a history of hemophilia in the maternal grandfather and the administration of factor VIII to a maternal aunt when subject to invasive procedures. Prolonged APTT was corrected with normal plasma pool. Factor VIII: 12%. We started substitution treatment with factor VIII, with a favorable evolution.Conclusions: haematoma of the psoas iliacus is a severe hemorrhage with high levels of morbi-mortality if no timely diagnosis or treatment is performed. Its clinical presentation with no apparent cause is an atypical manifestation of mild hemophilia. It is important not to underestimate the risk of bleeding in these patients, since they show greater morbimortality in the same clinical scenario compared with more severe presentations of the disease.
Keywords: Hemophilia A; Psoas muscles; Hematoma; Adolescent